2016
DOI: 10.1111/mms.12345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of the beaked whale genusBerardiusin the North Pacific, with genetic evidence for a new species

Abstract: There are two recognized species in the genus Berardius, Baird's and Arnoux's beaked whales. In Japan, whalers have traditionally recognized two forms of Baird's beaked whales, the common “slate‐gray” form and a smaller, rare “black” form. Previous comparison of mtDNA control region sequences from three black specimens to gray specimens around Japan indicated that the two forms comprise different stocks and potentially different species. We have expanded sampling to include control region haplotypes of 178 Bai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
0
30
0
1
Order By: Relevance
“…, Morin et al . ). The maximum reported body length for M. stejnegeri is 5.7 m, and two adult males of the new dwarf Berardius measured 6.6 and 7.3 m, respectively, compared to a maximum of 11.0 m for Baird's beaked whale ( Berardius bairdii ; MacLeod , Morin et al .…”
Section: Sightingsmentioning
confidence: 97%
“…, Morin et al . ). The maximum reported body length for M. stejnegeri is 5.7 m, and two adult males of the new dwarf Berardius measured 6.6 and 7.3 m, respectively, compared to a maximum of 11.0 m for Baird's beaked whale ( Berardius bairdii ; MacLeod , Morin et al .…”
Section: Sightingsmentioning
confidence: 97%
“…In response to these pressures, research, policy, and education or conservation awareness campaigns regarding marine megafauna conservation issues have increased considerably (Authier et al, 2017). However, while megafauna research, conservation policies, and education efforts have produced important results (Taylor et al, 2000;Boyd et al, 2016;Morin et al, 2016), we suggest that many efforts have yet to adequately embrace the complexity of the systems in which marine megafauna reside. Given the mounting pressure on ocean resources and the growing concerns regarding marine megafauna conservation (National Academy of Sciences, 2017), failing to acknowledge and account for this inherent complexity may hinder much needed advances and success in marine megafauna research and conservation.…”
Section: Introductionmentioning
confidence: 89%
“…Stranding records are the primary source of information for many elusive species, such as beaked whales (Ziphiidae; Morin et al . ) and can provide an indication of relative abundance and richness in extant cetacean communities (Evans and Hammond , Maldini et al . , Pyenson ).…”
Section: Potential Correlates Of Strandingsmentioning
confidence: 99%
“…Stranding records are the primary source of information for many elusive species, such as beaked whales (Ziphiidae; Morin et al 2017) and can provide an indication of relative abundance and richness in extant cetacean communities (Evans and Hammond 2004, Maldini et al 2005, Pyenson 2011). Globally, there are several long-term, regional stranding data sets: the northwest Pacific in the United States, e.g., Norman et al (2004) who reported 904 records, concluding that most reports are made in summer time when sampling effort is higher: Hawaii, e.g., Maldini et al (2005); who documented 202 odontocete strandings; the Netherlands, e.g., Murphy et al (2006) who have~10,000 strandings records to date, the majority of which are harbor porpoises; and Australia, e.g., Evans et al (2005), who analyzed 639 stranding events comprising 39 taxonomic groups.…”
mentioning
confidence: 99%